Tinjauan Terhadap Tindak Pidana Pelaku Kekerasan Seksual Yang Dilakukan Oleh Anak: Studi Di Pengadilan Tindak Pidana Kekerasan Seksual Pada Pengadilan Negeri Tanjung Karang - Prasetyawati, S. Endang; Rusli, Tami; Anindya D.S., Yolanda (Jurnal Hukum & Pembangunan, 2022)
Children are frequently the victims of sexual violence crime, but they can also commit sexual violence. The absence of parental monitoring led to this occurrence. The purpose of this study was to determine the research process on criminal acts of sexual violence committed by children and the judge’s considerations in cases of criminal acts of sexual violence committed by children. This study adopted a normative juridical approach as its methodology. Legal normative data sources, gathering information through outdoor investigation and library study. Data analysis employed legal qualitative. Accroding to the findings of the study and discussion, judges should take into account that children who commit crimes including sexual assault would receive a sentence that is only half that of an adult. The judge’s judgment tas taken in line with the law, and it was supported by three reliable pieces of evidence: witness accounts, documentary evidence from the Visum Et Repertum result, the defendant’s statement, and proof that the defendant used to commit sexual assault. Suggestion, the requirement for a more through investigation of children’s law in order to ensure the administration of the legal process in matters involving children. The PPPA service and the Criminal Investigation Unit PPA Unit Polresta Bandar Lampung are move involved in socializing, paying attention to, and educating families and communities about sexual abuse.